(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
When operating traction networks of electrified railways, a number of professions of operating personnel, as well as the population living along railway tracks, near objects servicing the operation of electrified railways, are adversely affected by the electromagnetic field caused by the operation of electric traction devices and requiring the development of protective technical means.